ANALISIS PELAKSANAAN BUDAYA LITERASI SEBAGAI STRATEGI DALAM MENUMBUHKAN KETERAMPILAN MEMBACA PESERTA DIDIK DI SEKOLAH DASAR - Agnestia, Rifany Sakura; Andriana, Encep; Hakim, Zerri Rahman (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the literacy culture program as a strategy to foster reading skills among students at SDN Tanjung Barat 04 Pagi. The research was conducted using a qualitative descriptive approach with data collection techniques including interviews, observations, and documentation. The data sources for this study were the class IA teacher, class IB teacher, and students from classes IA and IB. The results of the study indicate that the literacy culture program at SDN Tanjung Barat 04 Pagi is based on the School Literacy Movement guidelines through socialization organized by the Education Department. The implementation process of the literacy culture is aligned with the GLS program, and there are three stages: the first stage is habituation, the second stage is development, and the third stage is learning. Teachers are able to integrate literacy learning through teaching activities and utilize learning media as a literacy tool. Supporting factors for the literacy culture include the school principal's policy in actively implementing the School Literacy Movement within the school environment, as well as educators who are able to optimize literacy facilities and infrastructure. On the other hand, inconsistencies among teachers have become an obstacle faced by the school, along with the lack of professional English language teachers due to staff mutations. The outcome of implementing the literacy culture within the school environment has resulted in students developing reading skills, making them accustomed to reading activities. Students are able to understand the sentences they read, retell them in their own words, and contribute to a literacy-rich school environment. However, there are still some students in classes IA and IB who are unable to read, prompting teachers to provide additional teaching to improve the students' reading skills.